Pengaruh Financial Knowledge, Pendapatan dan Social influence terhadap Minat Menggunakan Aplikasi Pembayaran Digital pada Generasi Milenial Islam di Kota Bekasi - Milda Handayani; Muhammad Richo Rianto (ITB AAS INDONESIA Surakarta, 2021)
This study aims to know influence financial knoweldge, income and social influence on use intention digital payment apps of Islamic Millennial Generation in Bekasi. This study uses quantitative research with a interview method technique with a population islamic millennial generation in Bekasi City. The targeted unit of analysis is the Islamic millennial generation. There were 100 questionnaires returned and 5 of them did not meet the requirements, so only 95 were used in this study. This study uses SmartPLS 3.3 to test the hypothesis. Findings - This research shows that financial knowledge and social influence affect on use intention digital payment apps of Islamic Millennial Generation in Bekasi Islamic. But income shows does not affect on use intention digital payment apps of Islamic Millennial Generation in Bekasi. This research further reinforces that knowledge and environment are important factor in all business and industries. The focus of this research is the development of financial knowledge, income and social influence. This research was also unique because it is studied in an area with a muslim majority.